Mediating role of instructional and assessment strategies on learners' engagement in Educational statistics, in teachers' training colleges, Mfoundi division. - Arsene Tchocgnia Yanya (Mauve Journal De Leardu, 2024)
Cameroon, like many nations worldwide, is striving to achieve quality basic education and reduce the rate of school dropouts. In this process, teacher-trainers carry an immense responsibility of transmitting relevant and motivational skills to student teachers, ensuring that when they enter the field, they remain mindful of their role in shaping the nation builders of tomorrow. However, one cannot effectively train nation builders without first being a competent educator and critical thinker. This study was designed to examine the extent to which student teachers are responsive to instructional and assessment strategies that promote critical thinking and decision-making skills during field practice for the benefit of future generations. A total sample of 265 student teachers was selected from both a government and a private teacher training institution. Data were collected through questionnaires administered using simple random sampling, yielding a 74.8% response rate. The instrument contained 35 items addressing dependent and independent variables. Data analysis was conducted at the 0.05 significance level using correlation and regression with IBM SPSS version 21. The findings revealed that direct instruction, interactivity, quizzes, and portfolio assessments all correlated positively with student engagement. Quiz-mediated and portfolio-mediated interactivity emerged as the most effective strategies, suggesting that combining these methods offers the greatest potential for enhancing student engagement in educational statistics.